L’évaluation des mineurs délinquants : une entreprise peu axée sur la limitation de la récidive - Jessica Filippi (Sociétés et Jeunesses en Difficulté)
In 2013, assessment was at the heart of discussions at the consensus conference on limiting recidivism. The report resulting from these discussions recommended that “to be effective [assessment] should be based on new methods which will imply a change in professional practices” (Consensus Conference, 2013, 35). Risk-Need-Receptivity (RNR) and Good Lives Model (GLM) models for offender integrate an assessment process and a formulation of a case plan. Applying these models to people who have committed an offense has interesting results in limiting recidivism. Recently, the legal texts of the juvenile justice ministry and the juvenile criminal justice code suggest that rehabilitation programs should limit recidivism. Firstly, this study tries to understand the assessment practices of youth educators in the context of a socio-educational report which collects information about the offender and his/her situation. Secondly, the study analyses in this practice, what is most or least mobilised in the principles of RNR and GLM models. For this, the study combines quantitative data (250 socio-educational reports) with qualitative data (testimonies of youth educators about their practices (n=11). The results indicate on the one hand that the assessment process doesn’t follow a linear method because of exchanges and power games between the different actors of the assessment (offender, family, youth educators, magistrates…), and secondly that the RBR and GLM models are implemented in a partial way. The complete transposition of these models raises questions.